Outcomes of Patients with Behcet's Syndrome after Pulmonary Endarterectomy - YILDIZELİ, BEDRETTİN; CEYHAN, BERRİN; MUTLU, BÜLENT; DİRESKENELİ, RAFİ HANER; OLGUN YILDIZELİ, ŞEHNAZ (GEORG THIEME VERLAG KG, 2018)
Background Behcet's syndrome (BS) is a multisystem disorder and is not known as a risk factor for chronic thromboembolic pulmonary hypertension (CTEPH), for which the treatment of choice is pulmonary endarterectomy (PEA). The aim of this study was to review our experience in the surgical treatment of CTEPH in patients with BS. Methods Data were collected prospectively for consecutive patients with BS who underwent PEA over a 6-year period. Results We identified nine patients (seven males, two females, mean age: 34.79.9 years) with BS. The mean disease duration before PEA was 88.0 +/- 70.2 months. All patients but one received immunosuppressive therapy before the surgery. Exercise-induced dyspnea presented symptoms in six patients. One patient had associated intracardiac thrombosis. PEA was bilateral in five patients, unilateral in three, and lobar in one. No perioperative mortality was observed; however, one patient died four weeks after PEA due to massive hemoptysis. Morbidity was observed in two patients. The systolic pulmonary artery pressure fell significantly from 59.0 +/- 22.7mm Hg to 30.0 +/- 6.5mm Hg after surgery ( p =0.031). Pulmonary vascular resistance also improved significantly from 611.8 +/- 300.2 to 234.7 +/- 94.9 dyn/s / cm (5) ( p =0.031). After a median follow-up of 29.4 months, all patients improved to the New York Heart Association (NYHA) functional class I and II. Conclusion Patients with BS may suffer recurrent pulmonary embolism and develop CTEPH. In patients who do not respond to anticoagulation or immunosuppressive therapy, PEA may be a therapeutic option when thrombotic lesions are surgically accessible. Due to the high risk of perioperative mortality, the procedure should be undertaken in centers with experience.
Keywords: Behcet's syndrome; pulmonary endarterectomy; mortality; hemoptysis; outcome; ARTERY ANEURYSMS; DISEASE; HYPERTENSION